2016
DOI: 10.1039/c6sm00408c
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical investigations of non-Newtonian electro-osmotic driven flow in rectangular microchannels

Abstract: With the development of microfluidics, electro-osmotic (EO) driven flow has gained intense research interest as a result of its unique flow profile and the corresponding benefits in its application in the transportation of sensitive samples. Sensitive samples, such as DNA, are incapable of enduring strong flow shear induced by conventional hydrodynamic driven methods. EO driven flow is thus a niche area. However, even though there are a few research studies focusing on bio-fluidic samples related to EO driven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 43 publications
5
26
0
Order By: Relevance
“…One key factor for the experiments is the inclusion of a non-Newtonian fluid. For this purpose, dilute aqueous polymeric solutions such as polyethylene oxide or polyacrylamide can be mixed with the electrolyte solution and then stirred for 24 h (Huang et al 2016;Mukherjee et al 2017a). In this context, it is important to mention that the polymer concentration should remain in the dilute regime, i.e.…”
Section: Experimental Perspectivementioning
confidence: 99%
“…One key factor for the experiments is the inclusion of a non-Newtonian fluid. For this purpose, dilute aqueous polymeric solutions such as polyethylene oxide or polyacrylamide can be mixed with the electrolyte solution and then stirred for 24 h (Huang et al 2016;Mukherjee et al 2017a). In this context, it is important to mention that the polymer concentration should remain in the dilute regime, i.e.…”
Section: Experimental Perspectivementioning
confidence: 99%
“…Furthermore, in the analytical and numerical study on electroosmotic flow of viscoelastic fluid, Maxwell fluid model , Oldroyd‐B model , and the Phan–Thien–Tanner fluid model were also extensively considered to describe the rheological behavior of fluids. The experimental study on electroosmotic flow of non‐Newtonian fluids can also be found in .…”
Section: Introductionmentioning
confidence: 99%
“…[15] also used the power-law model to analyse the mixing flow in a contracting-expanding microchannel noting that mixing efficiency is decreased with decreasing rheological flow behaviour index. Huang et al [16] also employed the power-law model to confirm experimentally (via electrical current monitoring and microscopy fluorescence methods) that electroosmotic driven flow is enhanced with shear-thinning behaviour in rectangular microchannels. Jiménez et al [17] used the Maxwell viscoelastic model to simulate the electroflow of ionic solutions in rectangular microchannels with large asymmetric wall zeta potentials, addressing both relaxation time effect and noting that velocity assumes a transient oscillatory trend caused by the competition between viscous, elastic and electroosmotic forces.…”
Section: Introductionmentioning
confidence: 99%